2021
DOI: 10.3758/s13421-021-01218-6
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of impossible tests: Assessing the role of error-correction in the pretesting effect

Abstract: Relative to studying alone, guessing the meanings of unknown words can improve later recognition of their meanings, even if those guesses were incorrect – the pretesting effect (PTE). The error-correction hypothesis suggests that incorrect guesses produce error signals that promote memory for the meanings when they are revealed. The current research sought to test the error-correction explanation of the PTE. In three experiments, participants studied unfamiliar Finnish-English word pairs by either studying eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…In both experiments, pretesting produced clear improvements in target recognition memory, relative to Read-only trials. This pattern is consistent with previous observations using unfamiliar word definitions (Potts et al, 2019;Potts & Shanks, 2014;Seabrooke, Mitchell, Wills, Inkster, et al, 2021), semantically unrelated word pairs , and unrelated face-fact pairs . In tests of source memory, however, no effect of pretesting was observed, regardless of whether the source was assessed for target colour (Experiment 1) or temporal context (Experiment 2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In both experiments, pretesting produced clear improvements in target recognition memory, relative to Read-only trials. This pattern is consistent with previous observations using unfamiliar word definitions (Potts et al, 2019;Potts & Shanks, 2014;Seabrooke, Mitchell, Wills, Inkster, et al, 2021), semantically unrelated word pairs , and unrelated face-fact pairs . In tests of source memory, however, no effect of pretesting was observed, regardless of whether the source was assessed for target colour (Experiment 1) or temporal context (Experiment 2).…”
Section: Discussionsupporting
confidence: 92%
“…When participants incorrectly guessed the definitions of rare English words at encoding, they were more likely to correctly recognise the corrective feedback in a later test than if they had simply studied the definitions without generating a guess. This pattern is consistent with previous results (Potts et al, 2019;Potts & Shanks, 2014;Seabrooke, Mitchell, Wills, Inkster, et al, 2021). The pattern also reiterates that, in contrast to earlier thoughts, pretesting can also improve memory for targets that were presented in semantically unfamiliar and unrelated word pairs, at least in target recognition tests.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This explanation would account for the finding that, when the guessing error and the target are semantically related, retrieval is enhanced [26,32,[35][36][37]. Other research however has found no effect or even a detrimental effect of guessing when unrelated word pairs were learned [30,31,[38][39][40]. As Metcalfe and Huesler [28] argue: "the notion that the benefit seen from the generation of errors in typical participants is attributable to semantic memory mediation sits awkwardly with the findings that amnesics who are thought to have intact semantic memory but not episodic memory [41][42][43] do not similarly benefit" [28].…”
Section: Introductionmentioning
confidence: 99%
“…These guess trials are contrasted with study-only trials. Here, the question and answer are presented together with no pre-test (e.g., Clark et al, 2021;Cyr & Anderson, 2015Grimaldi & Karpicke, 2012;Hays et al, 2013;Huelser & Metcalfe, 2012;Knight et al, 2012;Metcalfe & Huelser, 2020;Potts et al, 2019;Potts & Shanks, 2014;Seabrooke, Mitchell, Wills, Inkster et al, 2021;Zawadzka & Hanczakowski, 2019).…”
mentioning
confidence: 99%